Economic Shocks and Worker Careers: Has the COVID-19 Pandemic Affected Transitions Out of Unemployment? - Mara Buhmann; Laura Pohlan; Duncan H.W. Roth (Institute of Labor Economics (IZA), 2024)
Temporary economic shocks can have enduring effects on individuals and their career trajectories. This paper investigates the labour market effects of the Covid- 19 pandemic on newly unemployed individuals, the underlying mechanisms as well as occupation-specific effect heterogeneity. The results indicate long-lasting earnings losses due to the pandemic, which can be explained by a decline in employment in the short run and a decline in wages in the longer run. We further find that the lower the lockdown work ability of a worker's previous occupation, the greater the adverse effects of the pandemic.
Keywords: J23; J62; J64; 330; economic shocks; COVID-19; unemployment; worker careers; occupations